Tumor Suppressor Gene Inactivation during Cadmium-Induced Malignant Transformation of Human Prostate Cells Correlates with Overexpression of de Novo DNA Methyltransferase - Benbrahim-Tallaa, Lamia (National Institute of Environmental Health Sciences, 2007)
BACKGROUND: Aberrant DNA methylation is common in carcinogenesis. The typical pattern appears to involve reduced expression of maintenance DNA methyltransferase, DNMT1, inducing genomic hypomethylation, whereas increased expression of de novo DNMT3a or 3b causes gene-specific hypermethylation. OBJECTIVES: During cadmium-induced malignant transformation, an unusual pattern of genomic hypermethylation occurred that we studied to provide insight into the roles of specific DNMTs in oncogenesis. METHODS: Gene expression and DNA methylation were assessed in control and chronic cadmium-transformed prostate epithelial cells (CTPE) using reverse transcription–polymerase chain reaction (RT-PCR), Western blot analysis, methylation-specific PCR, and methyl acceptance assay. RESULTS: During the 10-weeks of cadmium exposure that induced malignant transformation, progressive increases in generalized DNMT enzymatic activity occurred that were associated with over-expression of DNMT3b without changes in DNMT1 expression. Increased DNMT3b expression preceded increased DNMT enzymatic activity. Procainamide, a specific DNMT1 inhibitor, reversed cadmium-induced genomic DNA hypermethylation. Reduced expression of the tumor suppressor genes, RASSF1A and p16, began about the time DNMT3b overexpression first occurred and progressively decreased thereafter. RASSF1A and p16 promoter regions were heavily methylated in CTPE cells, indicating silencing by hypermethylation, while the DNA demethylating agent, 5-aza-2′-deoxycytidine, reversed this silencing. DNMT1 inhibition only modestly increased RASSF1A and p16 expression in CTPE cells and did not completely reverse silencing. CONCLUSIONS: These data indicate that DNMT3b overexpression can result in generalized DNA hypermethylation and gene silencing but that DNMT1 is required to maintain these effects. The pattern of genomic DNA hypermethylation together with up-regulation of DNMT3b may provide a unique set of biomarkers to specifically identify cadmium-induced human prostate cancers.